If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -5(x + -5) = -2 + 3x + -9 Reorder the terms: 2x + -5(-5 + x) = -2 + 3x + -9 2x + (-5 * -5 + x * -5) = -2 + 3x + -9 2x + (25 + -5x) = -2 + 3x + -9 Reorder the terms: 25 + 2x + -5x = -2 + 3x + -9 Combine like terms: 2x + -5x = -3x 25 + -3x = -2 + 3x + -9 Reorder the terms: 25 + -3x = -2 + -9 + 3x Combine like terms: -2 + -9 = -11 25 + -3x = -11 + 3x Solving 25 + -3x = -11 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 25 + -3x + -3x = -11 + 3x + -3x Combine like terms: -3x + -3x = -6x 25 + -6x = -11 + 3x + -3x Combine like terms: 3x + -3x = 0 25 + -6x = -11 + 0 25 + -6x = -11 Add '-25' to each side of the equation. 25 + -25 + -6x = -11 + -25 Combine like terms: 25 + -25 = 0 0 + -6x = -11 + -25 -6x = -11 + -25 Combine like terms: -11 + -25 = -36 -6x = -36 Divide each side by '-6'. x = 6 Simplifying x = 6
| 4.9x^2-20x+300=0 | | 4.9x*-20x+300=0 | | 4(2x+1)+7=7(4x-3) | | 5(q+2)+2q=1 | | -2x=-70 | | -3(x+9)=12 | | 23x-7=5 | | -4-3x=10x-6 | | 8h=16-6h | | 2d+4(3d+2)= | | 5a+3(a+4)= | | 9n-17=6n+7 | | 5(3x+4)=50 | | 2x+x+3x=6 | | -12,720+20x=0 | | 4x+(x+7)=-28-2x | | 5(x.2)=40/2 | | 1.6n=0.8n | | y=10x+4 | | 3x^4-30x^2-33=0 | | 4+2n=8n+16 | | -8+s=-56 | | 2x+y=-11 | | 7x=10x-5 | | 3.3=0.15x | | 6x+13=-17 | | 5(3p+2)-3(5p-3)= | | x+3x-5x-15= | | c+14=-13 | | 7y=6y-1 | | 7(r-4)-(-4+4r)=-r+4+2r | | (5x-7)(2x+1)-10x(x-4)=0 |